2021
DOI: 10.1111/srt.13119
|View full text |Cite
|
Sign up to set email alerts
|

How many skin barriers haveth we: Percutaneous egression of ions?

Abstract: Introduction: Skin provides critical barrier properties that enable terrestrial life. Myriad research has focused on the "water barrier" to transepidermal water loss (TEWL) despite there being a multitude of skin barrier properties. We asked what other barrier properties may have been overlooked and compiled data demonstrating the "electrolyte barrier" to be of potential clinical relevance.Methods: A literature search was conducted through PubMed, Embase, Google Scholar, and Web of Science databases for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Minimizing thermal sweating, hence, is crucial for quantifying TEWL under basal conditions. A low TEWL is a characteristic feature of a balanced, healthy skin protective state 6 . TEWL measurements can be used to assess the inside‐out barrier.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimizing thermal sweating, hence, is crucial for quantifying TEWL under basal conditions. A low TEWL is a characteristic feature of a balanced, healthy skin protective state 6 . TEWL measurements can be used to assess the inside‐out barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction, the TEWL has been applied in different fields of dermatological practice and research, as skin barrier physiology parameter in healthy and diseased skin, proof of concept for the cosmetic industry, monitoring therapeutic efficacy, occupational aspects of skin disease, and finally as a predictor for asthma and atopic dermatitis development 6–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been also reported that polymorphism in the thymic stromal lymphopoietin (TSLP) gene and its receptor, as well as dysregulation of genes involved in the metabolism of epidermal lipids, are associated with an increased risk of AD, its resistance, and food allergy. Other mutations of the skin barrier, including the SPINK5 gene and сorneodesmosin mutations, are also associated with AD and the development of food allergy [ 7 , 11 ]. Newborns with increased transepidermal water loss (TEWL) in the first week of life had an increased risk of developing AD at 12 months of age [ 12 ].…”
Section: Introductionmentioning
confidence: 99%